Modern therapy of anogenital warts - A. A. Khryanin; S. V. Klyuchareva; O. A. Baftalovskaya; N. V. Lobzev; E. B. Pershchetskaya (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Modern views on human papilloma virus are presented. Actual approaches to diagnostics and treatment of patients with anogenital warts are discussed. Clinical cases of high efficiency of Imiquimodum (Keravort) in treating anogenital warts of men and women are illustrated.